An analysis on the law enforcement issues in combating counterfeit medicines in Malaysia / Mohd Syahir Mohd Saibon and Dellia Faiza Abdul Razak - Mohd Saibon, Mohd Syahir; Abdul Razak, Dellia Faiza (Faculty of Law, 2015)
This study aims to examine the law and enforcement issues in combating counterfeit medicines in Malaysia. The prevalence of counterfeit medicines in Malaysia has increased to as high as 3-6% of market value. In other developed countries such as the United States and the United Kingdom, the percentage of counterfeit medicines in the market is below 1% due to several reasons. The reasons are a wider scope of laws and stricter enforcement measures. In Malaysia, there are several laws that could be applied to address the problem of counterfeit medicines. The laws are the Sales of Drug Act 1952 and its Regulation, and the Trade Description Act 2011. In addition, several enforcement bodies, including the Pharmacy Enforcement Division of the Ministry of Health and the Enforcement Division of the Ministry of Domestic Trade, Cooperative and Consumerism have taken steps to curb this problem. However, despite the existence of the legal framework and the effort of such bodies, the problem of counterfeit medicines is still alarming which suggests the insufficiency of the law enforcement. Therefore, this study aims to investigate the law enforcement issues in curbing the matter. Adopting a qualitative approach of both doctrinal and empirical methods, the study found that there are several issues affecting the insufficiency of the enforcement of the legal framework in Malaysia. The issues are ranging from the legal, the investigation, the administrative, the technological and the operational issues. Therefore, this study demonstrates that the barriers in laws and enforcement measures have significantly contributed to the insufficient enforcement of the laws and the rising of the counterfeit medicines in Malaysia.